The Effect of Exposure to Bisphenol A on Spermatozoon and the Expression of Tight Junction Protein Occludin in Male Mice - Tingshuai Cao; Yuanchao Cao; Hongqiang Wang; Peitao Wang; Xinsheng Wang; Haitao Niu; Cuihua Shao (SAGE Publishing, 2020)
Although bisphenol A (BPA) has been associated with impaired spermatogenesis, the mechanisms remain unclear. Tight junction occludin plays important roles in spermatogenesis. The objective of the present study was to explore the effects of BPA exposure in adolescent mice. Male mice were orally treated with low-dose (0.05 mg/kg/d), middle-dose (5.0 mg/kg/d), or high-dose (50 mg/kg/d) BPA in corn oil from postnatal day (PND) 35 to 65. Animals were killed on PND 65 and PND 125. On PND 65, the sperm count, sperm motility, and the expression of occludin showed a dose-related decline. On PND 125, the sperm count, sperm motility, and the expression of occludin were in recovery. However, there remained significant decreases in these parameters in the 50 mg/kg/d group on PND 125 compared with the control. The dose-related effects on the measured parameters and occludin expression suggest an early suppressive or damaging effect on the blood-testis barrier followed by recovery after dosing ceased. At a BPA dose of 50 mg/kg/d, recovery did not occur, suggesting that higher doses of BPA may cause irreversible damage to reproduction in male mice.